2019
DOI: 10.1093/trstmh/trz104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of community health workers in the fight against malaria in the Central African Republic (2012–2017)

Abstract: Background This last decade’s ongoing conflict in the Central African Republic (CAR) has led to gradual and continuous destruction of health services. With severe gaps in qualified health professionals, community health workers (CHWs) have become essential to ensuring health care access to the affected population. This article aims to evaluate the effectiveness of a 10-y CHW program in the CAR. Methods Routine case management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Our review found evidence that CHWs lead to more widespread appropriate referrals for Gambiense-type human African trypanosomiasis ( Palmer et al. , 2014 ) and malaria ( Ferdinand et al. , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review found evidence that CHWs lead to more widespread appropriate referrals for Gambiense-type human African trypanosomiasis ( Palmer et al. , 2014 ) and malaria ( Ferdinand et al. , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…, 2019 ; Van Boetzelaer et al. , 2019 ; Ferdinand et al. , 2020 ) and one used a simulation model ( Stijntjes, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Politically, in recent years, different armed groups have been expanding their spheres of influence and controlling the country’s rich mineral resources through several rebellions, further contributing to violence and human rights abuses and causing serious political instability [ 3 ]. Economically, the CAR is a country with a population of only 4.8 million, of which more than 70% of the population are living in multidimensional poverty.…”
Section: Resultsmentioning
confidence: 99%
“…Second, although previous studies have demonstrated the important role of community health workers in rapid malaria diagnosis and treatment, the number and training of community health workers remain problematic due to ongoing conflict [ 3 ]. The WHO, the United Nations and the International Committee of the Red Cross (ICRC) have taken active steps.…”
Section: Resultsmentioning
confidence: 99%